Das sozialistische Buch. Multinationale Editionsreihen im europäischen Ostblock - Zajas, Paweł (Harrassowitz-Verlag, 2023)
The paper analyses the cultural-political conditions of multinational edition series that appeared or were planned in countries of the European Eastern Bloc from the mid-1970s. Attention is drawn to (i) the cultural-political context of the Helsinki Final Act, which gave a decisive impetus to the increased transfer of literature within the Eastern Bloc, (ii) the “Library of Victory” realized in the years 1975–1981, and (iii) the “Library of European Poetry of the Twentieth Century” initiated in 1976. All three aspects are developed using selected text constellations and unpublished archival material and related to general methodological-theoretical problems.
The socialist book: Multinational edition series in the European Eastern Bloc
Wydział Anglistyki
Keywords: socialist literary field; socialist transnationality; multinational edition series; Helsinki Final Act